2021
DOI: 10.3390/ijms22052292
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Naringenin on miRNA-mRNA Profiles in HepaRG Cells

Abstract: Naringenin, a natural flavonoid widely found in citrus fruits, has been reported to possess anti-oxidant, anti-inflammatory, and hepatoprotective properties as a natural dietary supplement. However, the regulatory mechanism of naringenin in human liver remains unclear. In the present study, messenger RNA sequencing (mRNA-seq), microRNA sequencing (miRNA-seq), and real-time qPCR were used to distinguish the expression differences between control and naringenin-treated HepaRG cells. We obtained 1037 differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In the present study, we also demonstrated that chronic consumption of GFJ flavanones modulated the expression of 6 miRNAs in PBMCs, revealing for the first time the capacity of these compounds to act on these post-transcriptional regulators in humans. Citrus flavanones have been reported previously to modulate miRNA expression in preclinical models ( 20 , 55 , 56 ), however, data on the impact of these citrus bioactives on miRNA are still limited. MiRNAs have been identified as the important regulators of vascular function, which deregulation seems to contribute to vascular dysfunction and CVD development ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also demonstrated that chronic consumption of GFJ flavanones modulated the expression of 6 miRNAs in PBMCs, revealing for the first time the capacity of these compounds to act on these post-transcriptional regulators in humans. Citrus flavanones have been reported previously to modulate miRNA expression in preclinical models ( 20 , 55 , 56 ), however, data on the impact of these citrus bioactives on miRNA are still limited. MiRNAs have been identified as the important regulators of vascular function, which deregulation seems to contribute to vascular dysfunction and CVD development ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed selectively increased let-7g expression in NGN-treated NPC cells. A recent study using human hepatoma HepaRG cells found that NGN suppressed the activity of oncogenic metabolism through the regulation of miRNA-targeted mRNA expression inhibiting PI3K–Akt signaling [ 62 ]. The reported evidence indicates that the expression of has-miR-1306-5p, has-miR-627-3p, has-miR-194-3p, has-miR-676-3p, has-miR-6837-5p, has-miR-429, has-miR-100-3p, has-miR-194-5p, has-miR-519a-3p, has-miR-7-5p, and has-miR-200a-5p was involved in the attenuation of the PI3K–Akt signaling pathway of HepaRG cells by NGN [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using human hepatoma HepaRG cells found that NGN suppressed the activity of oncogenic metabolism through the regulation of miRNA-targeted mRNA expression inhibiting PI3K–Akt signaling [ 62 ]. The reported evidence indicates that the expression of has-miR-1306-5p, has-miR-627-3p, has-miR-194-3p, has-miR-676-3p, has-miR-6837-5p, has-miR-429, has-miR-100-3p, has-miR-194-5p, has-miR-519a-3p, has-miR-7-5p, and has-miR-200a-5p was involved in the attenuation of the PI3K–Akt signaling pathway of HepaRG cells by NGN [ 62 ]. The involvement of NGN-induced miRNAs in the negative regulation of PI3K–Akt-mediated anti-oxidative stress and ameliorative metabolism was postulated to be associated with the down-regulation of platelet-derived growth factor receptor β, phosphoenolpyruvate carboxykinase 1, cAMP-responsive element-binding protein 3 like 1, and nuclear factor kappa B mRNA expression targeted by has-miR-1306-5p or has-miR-627-3p [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation